COMBINATION OF POWER AND KWL STRATEGIES TO TEACH WRITING - Ichsanira Purwandari; Sri Wiyanah (Universitas PGRI Yogyakarta, 2020)
The aim of the study was to identify the effectiveness of using the combination of POWER and KWL to teach writing of fourth semester students at English Language Education Study Program in the University of PGRI Yogyakarta. It is based on the research problem that the students got difficulties on writing because they used ineffective strategy. The research used experimental research design. This research was conducted in 3 stages: data collection, action and data analysis. The data were collected through test, observation, and questionnaire. The data were analyzed using the steps of: normality test, homogeneity test, inferential analysis, determining hypothesis testing, and conclusion.The hypothesis is determined into the Null hypothesis (H0) and Alternative Hypothesis (Ha). H0 is accepted if the significance value >0.05 and Ha is rejected. The result of this research presented that the combination of POWER and KWL strategy was effective to teach writing at the university level. The control group’s mean score on the pre-test was 56,22 increased to 57,88 in post-test with gained point 1,59. The experiment group’s mean score on pre-test was 57,33 increased to 60,89 on post-test with gained point 3,66.